The Relevance of Collision Tests and Quantitative Sensory Testing in Diagnostics and Postoperative Outcome Prediction in Carpal Tunnel Syndrome - Koszewicz, Magdalena; Szydlo, Mariusz; Gosk, Jerzy; Wieczorek, Malgorzata; Slotwinski, Krzysztof; Budrewicz, Slawomir (Frontiers in Neurology, 2022)
Background: The gold standards for the diagnosis and treatment of carpal tunnel syndrome (CTS) and its outcome are undecided. Using clinical and electrophysiological methods, we tried to establish which fibers achieved full postoperative recovery, and the possibility of using non-standard electrophysiological tests as outcome predictors. Methods: The study group consisted of 35 patients and controls. The Historical–Objective Scale, standard neurography, conduction velocity distribution tests (CVD), and quantitative sensory testing (QST) were performed before and after CTS surgery. Results: Clinical improvement was observed on average in 54.3% of the patients, higher in less advanced CTS. All parameters improved significantly after surgery, except for CVD; most remained worse than in the controls. Only QST parameters fully returned to normal limits. Patient age and CTS severity were important in the estimation of the risk of no improvement. Conclusions: The efficiency of minimally invasive CTS surgery is higher in younger patients with less advanced CTS. Complete recovery was present only in small fibers; larger fibers could most likely be responsible for residual signs. We did not notice any benefits in CTS diagnosis using methods of small fiber assessment. QST seemed to be useful in the diagnosis of residual signs, and in deciding upon possible reoperation.